Coronavirus Disease 2019 (Covid-19) Dampak Covid-19 Terhadap Masyarakat Comorbid Dan Perekonomian Masyarakat Di Desa Dukuhwaluh, Kecamatan Kembaran, Kabupaten Banyumas - Anisa Ika Marliana; Amara Auliafani; Rama Wahyu Prasetyo; Bunga Olivia; Cinthia Dewi (UM Purwokerto Press, 2021)
Coronavirus disease 2019 (COVID-19) is a viral pneumonia disease that first spread in Wuhan, China, in December 2019. People with comorbid diseases are one of the groups that are very vulnerable to exposure to the virus during the Covid-19 pandemic. Some accompanying diseases include hypertension, diabetes mellitus and heart disease. The impact on the economic sector in Indonesia as a result of this pandemic include layoffs, decreased imports, and rising prices (inflation). In the midst of the Covid-19 pandemic, students of Geography Education of Muhammadiyah University of Purwokerto contributed to help ease the economic burden of the people of Dukuhwaluh Village by providing social assistance. The method used in this activity is a questionnaire to find out the comorbid suffered as well as the decline of the respomden economy. Previously, students were assisted by a special team of Dukuhwaluh Village in selecting community data that has comorbid. As many as 30 people who have congenital diseases that are vulnerable to Covid-19. Based on the data obtained, the most common comorbid suffered by the community is hypertension.